ENTREPRENEURIAL MINDSET IN MODERN APPAREL: THE ROLE OF MACHINE LEARNING IN DRIVING SUSTAINABLE INNOVATION - Nishtha Ujjawal; Manisha Gupta; Shagun Sharma; Hari Shankar Shyam (Proceedings on Engineering Sciences, 2024)
The apparel industry is on the cusp of a significant transformation, driven by an entrepreneurial spirit that embraces innovative approaches and sustainable practices. This study investigates the incorporation of ML in the contemporary apparel industry, highlighting its potential to promote transformative sustainable practices. Focusing on garment firms, the study demonstrates how ML is being used to be Source eco-friendly materials, reduce waste ,improve energy efficiency, increase supply chain transparency. The study also draws on qualitative insights from industry experts to identify the possibilities and challenges of integrating ML within the apparel industry. Overall, the study highlights the paradigm shift underway in the apparel industry, driven by an entrepreneurial mindset and facilitated by ML technology. This study functions as a guiding light, directing policymakers, industry leaders, and academics towards the advancement of a balanced integration of ML and sustainable entrepreneurship in modern apparel practices.